1992
DOI: 10.1007/bf00012875
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen form on maize response to drought stress

Abstract: Two hybrids of maize (Zea mays L.) differing in resistance to drought, were grown in chernozem soil in a greenhouse and were fertilized with two different forms of nitrogen: Ca(NO3) 2 and (NH4)2SO 4 in concentrations corresponding to 100 kg of N ha z. After emergence of the 4th leaf, plants were exposed to drought. During the drought period, the parameters of plant water status (water potential, osmotic potential, turgor pressure and relative water content) and chlorophyll a + b concentration were monitored ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1996
1996
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 14 publications
1
10
0
Order By: Relevance
“…NH 4 treated plants maintain the high turgor by improved osmotic adjustment under drought stress. Whereas, chlorophyll a, b values significantly higher in NH 4 treated plants compared to NH 3 treated plants in which chlorophyll content decreased throughout the drought stress [23]. Similar work Zhang et al [101] indicated increased NO 3 nutrition played a favored anti-oxidative metabolic role, as compared with NH 4 nutrition, in the plants thereby increasing tolerance to drought stress.…”
Section: Effect Of Nitrogen At Vegetative Stage Under Drought Stresssupporting
confidence: 68%
See 1 more Smart Citation
“…NH 4 treated plants maintain the high turgor by improved osmotic adjustment under drought stress. Whereas, chlorophyll a, b values significantly higher in NH 4 treated plants compared to NH 3 treated plants in which chlorophyll content decreased throughout the drought stress [23]. Similar work Zhang et al [101] indicated increased NO 3 nutrition played a favored anti-oxidative metabolic role, as compared with NH 4 nutrition, in the plants thereby increasing tolerance to drought stress.…”
Section: Effect Of Nitrogen At Vegetative Stage Under Drought Stresssupporting
confidence: 68%
“…Moreover, shortage and N excess affect assimilate partitioning between vegetative and reproductive organs [22]. Mineral nutrition influences the physiological response of plants to water stress [23]. While Waraich et al [24] discussed the role of macro-and micronutrients to decrease the adverse effect of drought in crop plants.…”
Section: Introductionmentioning
confidence: 99%
“…It is also possible that cells from non‐fertilized plants may accumulate osmotically active substances (K + ) as it was found in maize with low doses of nitrate and ammonium (Mihailović et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of chlorophyll and carotenoid pigments was rather low, which may be indicative of a moderate intensity of drought stress. On the other hand, chlorophyll content in the wheat leaves during drought is dependent on the type of N ions present in the nutrient solution [26]. An initial increase of the chlorophyll content during drought took place in the presence of NH 4+ , which was followed by a decrease in severity of the drought.…”
Section: Gas Exchangementioning
confidence: 99%